A new trisaccharide derivative from Prenanthes purpurea - Michaela Posch and Karin Jöhrer and Serhat Sezai Cicek and Richard Greil and Ernst P. Ellmerer and Christian Zidorn (Journal of the Serbian Chemical Society, 2011)
A methanolic extract of Prenanthes purpurea L. leaves yielded 1,6"- -di-O-cinnamoyl-β-D-glucopyranosyl-(1→3)-O-α-L-rhamnopyranosyl- (1→6)- -O-β-D-glucopyranoside. The NMR and physical data of this new natural compound are reported.
Keywords: Asteraceae; Cichorieae; Hypochaeridinae; Phenolic acids; Prenanthes purpurea L.; Trisaccharides